Novel Parameterized Score Functions on Interval-Valued Intuitionistic Fuzzy Sets with Three Fuzziness Measure Indexes and Their Application - Zhang, F. (Institute of Electrical and Electronics Engineers Inc., 2022)
10.1109/ACCESS.2018.2885794